The controversy over divine speech and the creation of the Qur’an between the Mu’tazila and the Hanbali in the era of the Abbasid caliphate (Journal of the College of Basic Education, 2023)
The controversy between groups and sects in Islamic societies was one of the intellectual contentious topics in the culture of Islamic societies, which was the result of (rationalism) and the different and private visions of the scholars and jurists (rationalists) of the two Mu’tazila schools. Unilateralism and the form of the individual’s vision in the Islamic society forever, and this is because the controversy was built largely on an intellectual and philosophical structure, and the debate contained in this field is partly attached to (theology) and divine knowledge and theology is a vague dialectical characteristic. It is noted that the controversy between the two groups has led to the euphoria of continuous division between them until now.